Hybrid Coronary Revascularization Versus Off‐Pump Coronary Artery Bypass Grafting: Comparative Effectiveness Analysis With Long‐Term Follow‐up. Issue 24 (December 2019) - Hage, Ali; Giambruno, Vincenzo; Jones, Philip; Chu, Michael W.; Fox, Stephanie; Teefy, Patrick; Lavi, Shahar; Bainbridge, Daniel; Harle, Christopher; Iglesias, Ivan; Dobkowski, Woijtecj; Kiaii, Bob
Abstract : Background: Hybrid coronary revascularization (HCR) involves the integration of coronary artery bypass grafting (CABG) and percutaneous coronary intervention to treat multivessel coronary artery disease. Our objective was to perform a comparative analysis with long‐term follow‐up between HCR and conventional off‐pump CABG. Methods and Results: We compared all double off‐pump CABG (n=216) and HCR (n=147; robotic‐assisted minimally invasive direct CABG of the left internal thoracic artery to the left anterior descending artery and percutaneous coronary intervention to one of the non–left anterior descending vessels) performed at a single institution between March 2004 and November 2015. To adjust for the selection bias of receiving either off‐pump CABG or HCR, we performed a propensity score analysis using inverse‐probability weighting. Both groups had similar results in terms of re‐exploration for bleeding, perioperative myocardial infarction, stroke, blood transfusion, in‐hospital mortality, and intensive care unit length of stay. HCR was associated with a higher in‐hospital reintervention rate (CABG 0% versus HCR 3.4%; P =0.03), lower prolonged mechanical ventilation (>24 hours) rate (4% versus 0.7%; P =0.02), and shorter hospital length of stay (8.1±5.8  versus 4.5±2.1 days; P <0.001). After a median follow‐up of 81 (48–113) months for the off‐pump CABG and 96 (53–115) months for HCR, the HCR group of patients had a trend toward improved survival (85% versus 96%; P =0.054). Freedom from any form of revascularization was similar between the 2 groups (92% versus 91%; P =0.80). Freedom from angina was better in the HCR group (73% versus 90%; P <0.001). Conclusions: HCR seems to provide, in selected patients, a shorter postoperative recovery, with similar excellent short‐ and long‐term outcomes when compared with standard off‐pump CABG.